Cancer-before-cancer: Mythologies of cancer in everyday life (Medicine Anthropology Theory, 2018)
Approaching the presence of cancer in everyday life in terms of mythologies, the article examines what cancer is and how cancer-related potentialities are enacted and embodied in the context of contemporary regimes of anticipation. Based on ethnographic fieldwork in a suburban Danish middle-class community among people who were not immediately afflicted by cancer, we describe different and paradoxical cancer mythologies and show how they provide multiple ways of understanding, anticipating, and dealing with cancer in everyday life. Special attention is paid to the relation between biomedically informed notions of symptoms and bodily processes, and a ghostly and muted presence of cancer, particularly when people are faced with more tangible cancer worries. We explore how contemporary cancer disease-control strategies emphasising ‘symptom awareness’ interweave with and add to cancer mythologies. We suggest that these strategies also carry moral significance as directives (be aware of early signs of cancer and seek care in time), and create an unintended illusion of certainty that does not correspond with everyday embodied forms of uncertainty and ambiguity. We argue that paying attention to the continuous cultural configurations of cancer that exist ‘before cancer’ will increase understanding of how the public health construction of ‘cancer awareness’ relates to everyday health practices such as symptom experience and health care seeking.